Penggunaan Fly Ash dan POFA sebagai Filler dalam Modifikasi Campuran Aspal Hotmix AC-BC - ST., MT, Syaifuddin Din; Kurniati, Kurniati; Gusrizal, Gusrizal; Miswar, Miswar; Ulfa, Nadia (Politeknik Negeri Lhokseumawe, 2025)
This study evaluates the use of POFA (Palm Oil Fuel Ash) and Fly Ash as fillers in Asphalt Concrete-Binder Course (AC-BC) mixtures. POFA was sourced from palm oil processing plants, while Fly Ash was obtained from coal-fired power plants. The research aims to identify the optimal filler composition by varying the proportions of POFA and Fly Ash, ranging from 0% to 100% POFA. Marshall parameter tests were conducted to assess stability, flow, VIM (Void in Mix), VMA (Void in Mineral Aggregate), and Marshall Quotient. The results show that POFA significantly improves the stability of the asphalt mixture compared to Fly Ash, with the highest stability observed at 100% POFA. However, increasing the amount of POFA also led to higher VIM values, indicating more air voids within the asphalt mixture, which could affect its long-term durability. The combined use of POFA and Fly Ash as fillers demonstrates that both can be utilized in AC-BC asphalt mixtures without compromising quality or failing to meet the 2018 Bina Marga specifications. The study concludes that POFA is a viable alternative filler for asphalt mixtures, particularly for improving the stability and performance of surface layers in road construction.